Numerical Solution of The Free Convection Boundry Layer Flow Over a Horizontal Circular Cylinder With Convective Boundry Conditions - Norhafizah, Md Sarif; Mohd Zuki, Salleh; Razman, Mat Tahar; Roslinda, Nazar (2013)

(untitled)
Numerical solution for steady free convection boundary layer flow near the lower stagnation point of a horizontal circular cylinder subjected to a convective boundary condition, where heat is supplied to the fluid through a bounding surface with a finite heat capacity are presented in this paper. The governing boundary layer equation are transformed using non-similar variables into non-similar equations and were solved numerically using an implicit finite difference scheme known as Keller-box method. The solution obtained for the skin friction coefficient, the local wall temperature, as well as the velocity and temperature profile with two the variations of two parameters, namely the conjugate parameter y and the Prandtl number Pr